The Effect of Discovery Learning Model on Students’ Ability to Write Fantasy Stories - Nia Noviani; Missriani Missriani; Dessy Wardiyah (Yayasan Karinosseff Muda Indonesia, 2020)
This study aims to determine whether there is an effect of the Discovery Learning model on improving the ability to write fantasy stories of seventh grade students of SMP Negeri 1 Prabumulih. This research is an experimental research (Experimental Research). Data collection techniques using observation, tests and documentation. The data analysis technique used independent samples t test. The results stated that 1) The ability to write fantasy stories of seventh grade students of SMP Negeri 1 Prabumulih after using the Discovery Learning learning model was in the high category. Then the ability to write fantasy stories using conventional learning models is in the high enough category; 2) There is an effect of the Discovery Learning learning model on the ability to write fantasy stories of VII grade students of SMP Negeri 1 Prabumulih based on the average value of the ability to write fantasy stories of seventh grade students of SMP Negeri 1 Prabumulih after using the Discovery Learning learning model which is higher than the ability to write fantasy stories of students which uses conventional amounting to 90.00. Therefore, it can be that the Ho3 hypothesis is accepted, meaning that there is an influence of the Discovery Learning Model on the ability to write fantasy stories of seventh grade students of SMP Negeri 1 Prabumulih.